1999
DOI: 10.1161/01.atv.19.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Prothrombin Gene 20201 GA Variant in FV:Q 506 Carriers in Relationship to the Presence or Absence of Juvenile Venous Thromboembolism

Abstract: Abstract-The G20210A transition of the prothrombin gene has been identified as a common but probably mild hereditary risk factor for venous thromboembolism (VTE). However, the prothrombin gene variant might contribute to the penetrance of thromboembolic disease in many patients with other prothrombotic defects, such as the FV:R506Q mutation. In this investigation, the A20210 allele was found in 9 of 450 healthy controls (2%). Among 89 asymptomatic FV:Q 506 carriers, 3 subjects were doubly affected (3.4%). In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 37 publications
3
23
1
1
Order By: Relevance
“…20 The prevalence of MTHFR1298 mutation in our study was comparable to the wide range of incidence reported in the United States population. 33 Previous studies have reported an increased prevalence of FVL and MTHFR mutations in neonates and children with thrombosis compared to the general population 16,34 and have also shown an increased risk of catheter-related thrombosis in patients with FVL; 12,13 however, we found no difference in the prevalence of MTHFR mutations and FVL mutation in infants with and without thrombosis.…”
Section: Discussioncontrasting
confidence: 45%
“…20 The prevalence of MTHFR1298 mutation in our study was comparable to the wide range of incidence reported in the United States population. 33 Previous studies have reported an increased prevalence of FVL and MTHFR mutations in neonates and children with thrombosis compared to the general population 16,34 and have also shown an increased risk of catheter-related thrombosis in patients with FVL; 12,13 however, we found no difference in the prevalence of MTHFR mutations and FVL mutation in infants with and without thrombosis.…”
Section: Discussioncontrasting
confidence: 45%
“…However, these observations suggest that combined defects of the prothrombin G20210A variant and further prothrombotic risk factors play an important role not only in adult carriers but also in young patients. 12,15,16 Thrombosis during childhood is frequently discussed as being due to nongenetic endogenous or exogenous trigger mechanisms. [17][18][19][20] Because in our study Ϸ62% of patients with thrombosis had an underlying disease, we can support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Moreover, the recently described G20210A mutation within the 3Ј-untranslated region of the prothrombin gene is a common but probably mild risk factor of venous thrombosis. [11][12][13][14][15][16] However, because of the low incidence of childhood vascular accidents, the role of such genetic defects in the childhood population is unclear.…”
mentioning
confidence: 99%
“…Based on various trials, evidence is accumulating that familial thrombophilia, defined as a genetically determined tendency to thrombosis, may be as a result of a combination of clotting defects (Ehrenforth et al, 1999b;Nowak-Go Èttl et al, 1999;Salomon et al, 1999). In particular, evidence has shown that inheritance of FV G1691A combined with deficiencies of protein C, protein S and anti-thrombin, as well as with the PT G20210A variant, the MTHFR T677T genotype in some studies, or enhanced Lp(a) concentrations, further increases the manifestation of early vascular accidents in children and young adults.…”
Section: Risk Factorsmentioning
confidence: 99%